Neurovascular Treatment in Improving Peripheral Perfusion in Diabetes Mellitus Patients - Shazhabilla, Neice Shieva; Septiyanti, Septiyanti (Indonesian Journal of Global Health Research, 2024)
Diabetes Mellitus (DM) is a long-term metabolic disorder caused by insulin function insufficiency, with many etiologies characterized by hyperglycemia accompanied by problems with carbohydrate, lipid, and protein metabolism. More than 90% of DM patients experience neuropathy complications and 50% experience peripheral neuropathy. DM patients with peripheral neuropathy experience decreased peripheral nerve perfusion so that neurovascular care is needed. Objective: This study was conducted to provide an overview of neurovascular care in improving peripheral perfusion in DM patients. Method: This study used a descriptive case study design using the nursing process. This study focuses on improving peripheral perfusion in DM patients with Neurovascular Care interventions to 2 respondens. The intervention carried out on two respondents according to the evidence base was foot exercises with diaball, foot spa, and ROM for 3 x 8 hours. The research instrument used is The Michigan Neuropathy Screening Instrument (MNSI) in assessing the complications of peripheral neuropathy which focuses on data on decreased peripheral perfusion and monofilaments to measure foot sensitivity. Results: Nursing activities start from assessing the patient's circulation needs and continue to data analysis. The data analyzed showed that >80% of the major and minor data listed in the guidelines for raising nursing diagnoses, namely the Indonesia Nursing Diagnose Standards (SDKI). From the data obtained, the diagnosis that can be raised is that peripheral perfusion nursing is ineffective with peripheral perfusion nursing outcomes with increased expectations. On the last day of the nursing evaluation, there was an increase in peripheral perfusion from a decreasing level to a moderate level in the respondents. Conclusions: Neurovascular Treatment can be applied to improve peripheral perfusion in DM patients.